Suggested languages for you:
|
|

## All-in-one learning app

• Flashcards
• NotesNotes
• ExplanationsExplanations
• Study Planner
• Textbook solutions

# Completing the Squares

When dealing with algebraic expressions, it is always helpful to view them in their simplest form. That way, we can solve these expressions easily and determine possible patterns involved. In this case, we want to look at simplifying quadratic equations. So far, we have learned factoring methods such as grouping and identifying the greatest common factor. In this article, we shall be introduced to a new concept called completing the square. We will see the steps for solving quadratic equations by completing the square and examples of its application.

## Complete Squares

Expressions of the form${\left(x+a\right)}^{2}and{\left(x-a\right)}^{2}$are known as a complete square.

Expanding the first expression, we obtain

${\left(x+a\right)}^{2}=\left(x+a\right)\left(x+a\right)={x}^{2}+2ax+{a}^{2}$.

Similarly, the second expression becomes

${\left(x-a\right)}^{2}=\left(x-a\right)\left(x-a\right)={x}^{2}-2ax+{a}^{2}$,

upon expansion.

Completing the square is a method used to simplify a quadratic equation into an algebraic expression that can be easily solved. This technique can also be used to determine the maximum or minimum values of a quadratic equation and help with graphing.

The aim here is to convert the standard form of a quadratic equation so that it looks like the expression above. The general formula for completing the square is as follows.

For the quadratic equation, $a{x}^{2}+bx+c=0,$ we can complete the square of this expression by converting this into the form

$a{\left(x-h\right)}^{2}+k=0$ ,

where$h=\frac{b}{2a}andk=c-\frac{{b}^{2}}{4a}$. This form is known as the vertex form of a quadratic.

## Geometrical Representation of Completing the Square

So what does it mean to complete the square? Before we get into some examples involving quadratic equations, it may be helpful to understand the geometry behind this method. Let us observe the diagram below.

Completing the square, Aishah Amri - StudySmarter Originals

In the first image, we have the red square and the green rectangle. Adding these two shapes together, we obtain the expression

${x}^{2}+bx$.

We want to rearrange this so that it looks like a square. Halving the width of the green rectangle, we obtain$\frac{{b}^{2}}{2}$.

Now rearranging these two new smaller green rectangles, we have the second image. Notice that we have a missing segment at the corner of the second image. Thus, to complete this square, we need to add the area of the blue square,${\left(\frac{b}{2}\right)}^{2}$. The complete square is shown in the third image. We can represent this algebraically as follows.

${x}^{2}+bx+{\left(\frac{b}{2}\right)}^{2}={\left(x+\frac{b}{2}\right)}^{2}$

where the term${\left(\frac{b}{2}\right)}^{2}$completes the square.

## Completing the Square for Quadratic Equations of the Form x2+ bx+ c

Here, we will deal with quadratic equations of the form x2 + bx + c, where the coefficient of the term x2 is 1.

### Balancing the Equation

From the previous section, it is important to note that we cannot add the term ${\left(\frac{b}{2}\right)}^{2}$without subtracting it from our initial expression. If we do not do this, our equation changes entirely. Let us show this with the following example.

Complete the square of the quadratic equation ${x}^{2}+4x+3=0$.

Solution

From the above equation, we have b = 4 and c = 3.

To complete the square, we have

${x}^{2}+4x\mathbf{+}{\mathbf{\left(}\frac{\mathbf{4}}{\mathbf{2}}\mathbf{\right)}}^{\mathbf{2}}+3\mathbf{-}{\mathbf{\left(}\frac{\mathbf{4}}{\mathbf{2}}\mathbf{\right)}}^{\mathbf{2}}=0$

Notice that we have to add ${\left(\frac{4}{2}\right)}^{2}$ and subtract ${\left(\frac{4}{2}\right)}^{2}$ to balance the equation. Now, observe that the first three terms above can be simplified into the form of a completed square as

${x}^{2}+4x+{\left(\frac{4}{2}\right)}^{2}={\left(x+\frac{4}{2}\right)}^{2}={\left(x+2\right)}^{2}$

Thus, the equation becomes

${x}^{2}+4x+3=0⇒{x}^{2}+4x+{\left(\frac{4}{2}\right)}^{2}+3-{\left(\frac{4}{2}\right)}^{2}=0⇒{\left(x+2\right)}^{2}-1=0$

As you can see, we've changed the equation from the standard form to vertex form with h = –2 and k = –1.

### Solving Completed Square Expressions

From the example above, observe that the variable x only appears once in the completed square expression. This allows us to solve the equation for x using basic algebra. Additionally, this means that we do not have to go through the hassle of performing the Quadratic Formula to solve a given quadratic equation. Let us return to the previous example.

Solve the equation${x}^{2}+4x+3=0$by completing the square.

Solution

Before, we found that

${x}^{2}+4x+3=0⇒{\left(x+2\right)}^{2}-1=0$

Solving for x, we obtain

${\left(x+2\right)}^{2}=1⇒x+2=±\sqrt{1}⇒x=±1-2⇒x=-1-2andx=1-2$

Thus, we obtain two solutions $x=-3andx=-1$.

### A Quicker Way to Complete the Square

In some cases, the method above can be difficult to solve, especially when we are given quadratic equations with larger coefficients. It is always helpful to know a shortcut to make calculations faster. By completing the square, we want our expression to take the vertex form:

${\left(x-h\right)}^{2}+k$.

Expanding the first term of this expression yields the definition of a complete square. The equation now becomes,

${\left(x-h\right)}^{2}+k={x}^{2}-2hx+{h}^{2}+k$.

The trick here is to "force" our given quadratic equation so that it takes the form of the expression above. Let us attempt this method in the previous example.

Complete the square of the following quadratic equation:

${x}^{2}+4x+3=0$.

Solution

Given the quadratic equation above, use the expression ${x}^{2}+2hx+{h}^{2}+k$to express the left-hand side as ${\left(x+h\right)}^{2}+k$.

Aligning these two expressions, we have

${x}^{2}+4x+3=0{x}^{2}+2hx+{h}^{2}+k=0$

From here we can see that 4x must take the form of 2hx, so d = 2 since $2\left(2x\right)=4x.$

The constant 3 must take the form h2 + k and since we know that d = 2,

${\left(2\right)}^{2}+e=3⇒e=-1$

Thus, we obtain

${x}^{2}+4x+3=0⇒{\left(x+2\right)}^{2}-1=0$

as we have solved before.

Before we move on to the next section, let us show another worked example.

Use the complete the square method to solve the quadratic equation ${x}^{2}-6x-12=0$.

Solution

From the above equation, we have b = –6 and c = –12.

We then note that

${x}^{2}-6x\mathbf{+}{\mathbf{\left(}\frac{\mathbf{6}}{\mathbf{2}}\mathbf{\right)}}^{\mathbf{2}}-12\mathbf{-}{\mathbf{\left(}\frac{\mathbf{6}}{\mathbf{2}}\mathbf{\right)}}^{\mathbf{2}}=0$

Simplifying the first three terms as a complete square and solving, we obtain

${\left(x-\frac{6}{2}\right)}^{2}-21=0⇒{\left(x-3\right)}^{2}-21=0$

Now solving for x

${\left(x-3\right)}^{2}=21⇒x-3=±\sqrt{21}⇒x=±\sqrt{21}+3⇒x=-\sqrt{21}+3andx=\sqrt{21}+3$

Thus we have two solutions, correct to two decimals

$x=-\sqrt{21}+3\approx -1.58x=\sqrt{21}+3\approx 7.58$

## Completing the Square for Quadratic Equations of the Form ax2+ bx+ c

In this section, we will deal with quadratic equations of the form ax2 + bx + c, where the coefficient of the term x2 is not equal to 1. For this form of quadratic equation, we can follow the steps below to complete the square.

### Completing the Square

Step 1: Given the standard form of the quadratic equation $a{x}^{2}+bx+c=0,$ divide all terms by a, that is the coefficient of x2

${x}^{2}+\frac{b}{a}x+\frac{c}{a}=0$.

Step 2: Move the term $\frac{c}{a}$ to the right-hand side of the equation.

${x}^{2}+\frac{b}{a}x=-\frac{c}{a}$.

Step 3: Complete the square on the left-hand side of the equation. Balance the equation by adding the same value to the right-hand side

${x}^{2}+\frac{b}{a}x\mathbf{+}{\mathbf{\left(}\frac{\mathbf{b}}{\mathbf{2}\mathbf{a}}\mathbf{\right)}}^{\mathbf{2}}=-\frac{c}{a}\mathbf{+}{\mathbf{\left(}\frac{\mathbf{b}}{\mathbf{2}\mathbf{a}}\mathbf{\right)}}^{\mathbf{2}}⇒{\left(x+\frac{b}{2a}\right)}^{2}=-\frac{c}{a}+\frac{{\mathrm{b}}^{2}}{4{\mathrm{a}}^{2}}⇒{\left(x+\frac{b}{2a}\right)}^{2}=\frac{{b}^{2}-4ac}{4{a}^{2}}$

Step 4: Take the square root of both sides

$x+\frac{b}{2a}=±\sqrt{\frac{{b}^{2}-4ac}{4{a}^{2}}}=±\frac{\sqrt{{b}^{2}-4ac}}{\sqrt{4{a}^{2}}}⇒x+\frac{b}{2a}=±\frac{\sqrt{{b}^{2}-4ac}}{2a}$

Step 5: Solve to find x

$x=±\frac{\sqrt{{b}^{2}-4ac}}{2a}-\frac{b}{2a}⇒x=\frac{-b±\sqrt{{b}^{2}-4ac}}{2a}$

Notice that we have derived the Quadratic Formula using the method of completing the square!

Now going back to Step 3, we have deduced that

${\left(x+\frac{b}{2a}\right)}^{2}=-\frac{c}{a}+{\left(\frac{b}{2a}\right)}^{2}$

Bringing the terms from the right-hand side back to the left-hand side

${\left(x+\frac{b}{2a}\right)}^{2}+\frac{c}{a}-{\left(\frac{b}{2a}\right)}^{2}=0$

Multiplying the entire equation by a and simplifying, we obtain

$a{\left(x+\frac{b}{2a}\right)}^{2}+a\left(\frac{c}{a}\right)-a\left(\frac{{b}^{2}}{4{a}^{2}}\right)=0⇒a{\left(x+\frac{b}{2a}\right)}^{2}+c-\frac{{b}^{2}}{4a}=0$

Observe that the equation now takes the form $a{\left(x-h\right)}^{2}+k=0$ where

$h=\frac{b}{2a}andk=c-\frac{{b}^{2}}{4a}$

which is exactly the general form of completing the square for a quadratic equation as we have initially mentioned in the beginning. Below are some worked examples that demonstrate this.

Complete the square of $10{x}^{2}-2x+1=0$ and solve for x.

Solution

Step 1: Divide the expression by a = 10

${x}^{2}-\frac{2}{10}x+\frac{1}{10}=0⇒{x}^{2}-\frac{1}{5}x+\frac{1}{10}=0$

Step 2: Move the term $\frac{1}{10}$ to the other side

${x}^{2}-\frac{1}{5}x=-\frac{1}{10}$

Step 3: Complete the square and balance the equation ${x}^{2}-\frac{1}{5}x+{\left(-\frac{1}{2\left(5\right)}\right)}^{2}=-\frac{1}{10}+{\left(-\frac{1}{2\left(5\right)}\right)}^{2}⇒{x}^{2}-\frac{1}{5}x+{\left(\frac{1}{10}\right)}^{2}=-\frac{1}{10}+\frac{1}{100}⇒{\left(x-\frac{1}{10}\right)}^{2}=-\frac{9}{100}⇒{\left(x-\frac{1}{10}\right)}^{2}+\frac{9}{100}=0$

Now multiplying the entire equation by a = 10, we obtain the vertex form

$10{\left(x-\frac{1}{10}\right)}^{2}+\frac{9}{10}=0$

Step 4: Taking the square root on both sides

$x-\frac{1}{10}=±\sqrt{-\frac{9}{100}}=±i\sqrt{\frac{9}{100}}=±\frac{3i}{10}$

Note: Remember that $\sqrt{-1}=i,\mathrm{sin}ce{i}^{2}=-1$

Step 5: Solving for x,

$x=±\frac{3i}{10}+\frac{1}{10}$

Thus, we have two solutions

$x=\frac{-3i+1}{10}andx=\frac{3i+1}{10}$

Complete the square of $-3{x}^{2}-4x+8=0$and solve for x.

Solution

Step 1: Divide the expression by a = –3

${x}^{2}-\frac{4}{\left(-3\right)}x+\frac{8}{\left(-3\right)}=0⇒{x}^{2}+\frac{4}{3}x-\frac{8}{3}=0$

Step 2: Move the term $-\frac{8}{3}$ to the other side

${x}^{2}+\frac{4}{3}x=\frac{8}{3}$

Step 3: Complete the square and balance the equation

${x}^{2}+\frac{4}{3}x+{\left(\frac{4}{2\left(3\right)}\right)}^{2}=\frac{8}{3}+{\left(\frac{4}{2\left(3\right)}\right)}^{2}⇒{x}^{2}+\frac{4}{3}x+{\left(\frac{2}{3}\right)}^{2}=\frac{8}{3}+{\left(\frac{2}{3}\right)}^{2}⇒{\left(x+\frac{2}{3}\right)}^{2}=\frac{28}{9}⇒{\left(x+\frac{2}{3}\right)}^{2}-\frac{28}{9}=0$

Now multiplying the entire equation by a = –3, we obtain the vertex form

$-3{\left(x+\frac{2}{3}\right)}^{2}+\frac{28}{3}=0$

Step 4: Taking the square root on both sides

$x+\frac{2}{3}=±\sqrt{\frac{28}{9}}=±\frac{2\sqrt{7}}{3}$

Step 5: Solving for x,

$x=±\frac{2\sqrt{7}}{3}-\frac{2}{3}=\frac{±2\sqrt{7}-2}{3}$

Therefore, we have two solutions

$x=\frac{-2\left(\sqrt{7}+1\right)}{3}and\frac{2\left(\sqrt{7}-1\right)}{3}$

## Identifying the Maximum and Minimum Values of a Quadratic Equation

Completing the square also helps us determine the maximum and minimum values of a given quadratic equation. By doing so, we can locate this value and plot the graph of a quadratic equation more accurately.

The vertex is a point at which the curve on a graph turns from decreasing to increasing or from increasing to decreasing. This is also known as a turning point.

The maximum value is the highest point of the curve in a graph. This is also known as the maximum turning point or local maxima.

The minimum value is the lowest point of the curve in a graph. This is also known as the minimum turning point or local minima.

For the general form of a quadratic equation, the maximum and minimum values on a graph take on the following two conditions.

A general plot of the maximum and minimum values of a quadratic equation, Aishah Amri - StudySmarter Originals

Essentially, if the coefficient of x2 is positive, then the graph curves downwards and if the coefficient of x2 is negative, then the graph curves upwards. From the general formula of completing the square, when the coefficient of x2 is 1,

${\left(x-h\right)}^{2}+k=0$,

the x and y coordinates of the turning point, or the vertex, can be found by the point (h, k). Similarly, when the coefficient of x2 is not 1,

$a{\left(x-h\right)}^{2}+k=0$,

the x and y coordinates of the turning point, or the vertex, can be found by the same point, (h, k). Note that the value of a does not affect the position of the vertex!

Let us look for the maximum and minimum values for the last two examples from the previous section.

Determine whether the quadratic equation $10{x}^{2}-2x+1=0$ has a maximum or minimum value. Hence, find the coordinates of its turning point.

Solution

The coefficient of the term x2 is positive, as a = 10. Thus, we have a minimum value. In this case, the curve opens up. From the derivation of the completed square form of this expression, we obtain

$10{\left(x-\frac{1}{10}\right)}^{2}+\frac{9}{10}=0$.

Here, $x=\frac{1}{10}$.

Remember that the value of a does not vary the x-value of the vertex!

Thus, the minimum value is $\frac{9}{10}$ when $x=\frac{1}{10}$.

The coordinates of the minimum turning point is $\left(\frac{1}{10},\frac{9}{10}\right).$ The graph is shown below.

Determine whether the quadratic equation $-3{x}^{2}-4x+8=0$ has a maximum or minimum value. Hence, find the coordinates of its turning point.

Solution

The coefficient of the term x2 is negative, as a = –3. Thus, we have a maximum value. In this case, the curve opens down. From the derivation of the completed square form of this expression, we obtain

$-3{\left(x+\frac{2}{3}\right)}^{2}+\frac{28}{3}=0$.

Here, $x=-\frac{2}{3}$.

Thus, the maximum value is $\frac{28}{3}$ when $x=-\frac{2}{3}$.

The coordinates of the maximum turning point is $\left(-\frac{2}{3},\frac{28}{3}\right).$ The graph is shown below.

## Completing Squares - Key takeaways

• For the quadratic equation $a{x}^{2}+bx+c=0,$ the standard form of the completed square form is $a{\left(x-h\right)}^{2}+k=0$ where $h=-\frac{b}{2a}andh=c-\frac{{b}^{2}}{4a}$
• Completing the square is a method used to
2. Determine the maximum or minimum values
• To complete the square and solve the quadratic equation, we must
1. Divide the expression by the coefficient of x2
2. Move the third term to the right-hand side
3. Complete the square and balance the equation
4. Take the square roots of both sides
5. Solve for x
• If the coefficient of x2 is positive, then we have a minimum value.
• If the coefficient of x2 is negative, then we have a maximum value.
• The coordinates for the turning point is (h, k).

Completing the square is a method used to simplify a quadratic equation and determine the maximum or minimum values

To solve a quadratic equation by completing the square, we must

1. Divide the expression by the coefficient of x2
2. Move the third term to the right-hand side
3. Complete the square and balance the equation
4. Take the square roots of both sides
5. Solve for x

Yes, all quadratic equations can be solved by completing the square

The formula for completing the square is a(x–d)2+e=0, where d=–b/2a and e=c-b2/4a

To solve a quadratic equation by completing the square, we must

1. Divide the expression by the coefficient of x2
2. Move the third term to the right-hand side
3. Complete the square and balance the equation
4. Take the square roots of both sides
5. Solve for x

## Final Completing the Squares Quiz

Question

What is the purpose of completing the square of a quadratic equation?

To simplify a quadratic equation and determine the maximum or minimum values

Show question

Question

What are the five steps to solving a quadratic equation by completing the squares?

1. Divide the expression by the coefficient of x2
2. Move the third term to the right-hand side
3. Complete the square and balance the equation
4. Take the square roots of both sides
5. Solve for x

Show question

Question

If the coefficient of xis positive in a given quadratic equation, what kind of turning point do we obtain?

Minimum value

Show question

Question

If the coefficient of xis negative in a given quadratic equation, what kind of turning point do we obtain?

Maximum value

Show question

Question

What is the maximum value? What are other terms that describe this?

The maximum value is the highest point of the curve in a graph. This is also known as the maximum turning point or local maxima.

Show question

Question

What is the minimum value? What are other terms that describe this?

The minimum value is the lowest point of the curve in a graph. This is also known as the minimum turning point or local minima.

Show question

Question

What is a vertex? Is there another word that can be used to describe this?

The vertex is a point at which the curve on a graph turns. This is also known as a turning point.

Show question

Question

For a quadratic equation with a positive term in x2, what do the coordinates (-ad,e) tell us about the graph?

The curve has a minimum value of e at x=-ad

Show question

Question

For a quadratic equation with a negative term in x2, what do the coordinates (ad,e) tell us about the graph?

The curve has a maximum value of e at x=ad

Show question

Question

Can any quadratic equation be solved by completing the square?

Yes, all quadratic equation be solved by completing the square

Show question

60%

of the users don't pass the Completing the Squares quiz! Will you pass the quiz?

Start Quiz

## Study Plan

Be perfectly prepared on time with an individual plan.

## Quizzes

Test your knowledge with gamified quizzes.

## Flashcards

Create and find flashcards in record time.

## Notes

Create beautiful notes faster than ever before.

## Study Sets

Have all your study materials in one place.

## Documents

Upload unlimited documents and save them online.

## Study Analytics

Identify your study strength and weaknesses.

## Weekly Goals

Set individual study goals and earn points reaching them.

## Smart Reminders

Stop procrastinating with our study reminders.

## Rewards

Earn points, unlock badges and level up while studying.

## Magic Marker

Create flashcards in notes completely automatically.

## Smart Formatting

Create the most beautiful study materials using our templates.